Peran Guru dalam Meningkatkan Motivasi Belajar Peserta Didik Underachiever di MI Modern SAKTI permatahati IBU Kepatihan Tulungagung - Chasanatul Mardiyah; Nur Kholis (The Elementary Journal, 2023)
This research departs from the very complex phenomenon of the teacher's role in optimizing the potential of students. It is not uncommon for unrealized potential to become an obstacle in the learning process, such as being an underachiever. Through various roles, teachers try to help increase students' motivation to learn. The focus of this research is What is the role of the teacher as an educator, as a facilitator, and as an evaluator in increasing the learning motivation of underachiever students at MI Modern "SAKTI" Permatahati Ibu. Kepatihan Tulungagung. This research uses a qualitative approach using primary data sources and secondary data. Data collection techniques used observation, semi-structured interviews and documentation studies. The data that has been collected is then analyzed through three stages, namely data condensation, data presentation and drawing conclusions. Based on the results of research findings and discussions, it can be concluded that teachers can increase the learning motivation of Underachiever students by using learning tools according to students' needs, increasing teacher human resources by attending seminars and training, optimizing all existing facilities. to make it easier for students to learn, provide assistance according to conditions, and carry out evaluations according to student competency, conditional and continuous.